Gender Differences in Primary Teachers’ Metacognitive Awareness - Khan, Aiyaz Ahmad; Ahmad, Rasheed (THE PRIMARY TEACHER, 2025)
Metacognition involves reflecting on one’s own thinking processes, and the aim of the present study was to evaluate primary teachers’ levels of metacognitive awareness across different genders. Additionally, the study assessed the impact of teacher training on metacognitive awareness, comparing trained and untrained primary teachers by gender. The study sample included 79 primary school teachers from the Murshidabad district in West Bengal. Data was collected using the Metacognitive Awareness Inventory for Teachers (2011) and analysed using statistical techniques, including Mean, Standard Deviation (SD), and F-values. The results indicated that there were no significant differences in metacognitive awareness between male and female primary teachers overall. However, notable differences were found between trained male and female teachers in terms of their overall metacognitive awareness and in the monitoring subscale. For untrained primary teachers, significant differences were observed between genders in overall metacognitive awareness, as well as in the subscales of conditional knowledge and planning.